Clinical Features of Schizophrenia With Enhanced Carbonyl Stress - Miyashita, Mitsuhiro (Oxford University Press, 2014)
Accumulating evidence suggests that advanced glycation end products, generated as a consequence of facilitated carbonyl stress, are implicated in the development of a variety of diseases. These diseases include neurodegenerative illnesses, such as Alzheimer disease. Pyridoxamine is one of the 3 forms of vitamin B6, and it acts by combating carbonyl stress and inhibiting the formation of AGEs. Depletion of pyridoxamine due to enhanced carbonyl stress eventually leads to a decrease in the other forms of vitamin B6, namely pyridoxal and pyridoxine. We previously reported that higher levels of plasma pentosidine, a well-known biomarker for advanced glycation end products, and decreased serum pyridoxal levels were found in a subpopulation of schizophrenic patients. However, there is as yet no clinical characterization of this subset of schizophrenia. In this study, we found that these patients shared many clinical features with treatment-resistant schizophrenia. These include a higher proportion of inpatients, low educational status, longer durations of hospitalization, and higher doses of antipsychotic medication, compared with patients without carbonyl stress. Interestingly, psychopathological symptoms showed a tendency towards negative association with serum vitamin B6 levels. Our results support the idea that treatment regimes reducing carbonyl stress, such as supplementation of pyridoxamine, could provide novel therapeutic benefits for this subgroup of patients.